If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Log(6x + 4) = 2 Reorder the terms: goL(4 + 6x) = 2 (4 * goL + 6x * goL) = 2 (4goL + 6goxL) = 2 Solving 4goL + 6goxL = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + 4goL + 6goxL = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + 4goL + 6goxL = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-1 + 2goL + 3goxL) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + 2goL + 3goxL)' equal to zero and attempt to solve: Simplifying -1 + 2goL + 3goxL = 0 Solving -1 + 2goL + 3goxL = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 2goL + 1 + 3goxL = 0 + 1 Reorder the terms: -1 + 1 + 2goL + 3goxL = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2goL + 3goxL = 0 + 1 2goL + 3goxL = 0 + 1 Combine like terms: 0 + 1 = 1 2goL + 3goxL = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5(a-10)=45 | | 16=103a | | 24*.75y=18y | | 2x+49x-9x+21x+5x= | | (6x+4)=2 | | (u+4)10=80 | | 3+4=6x+x | | 4y+5=3(2y-7) | | 9(18x-3)= | | (q-9)4=8 | | 2ln(7x+6)+19 = 13 | | 4(z-4)+5z=6z+11 | | X+7x+1=0 | | 2.5z=10 | | 2(4X-7)+12=4X+14 | | x+2/4-2x+1/3=-x/6 | | -3(4x+2)=-8(6x+3) | | 9ab+9b-49b+8ab-12= | | 36x-1=0 | | -16x+12=39-7x | | 3z-1=2z | | 6x+38x+40=0 | | 2(x+4)+3(2x-5)=5 | | 5x+8x-20=40-7x | | 5x^2+b*x+5=0 | | 6x-12+6=0 | | 8x+5x-17=85-4x | | 8x-17x+9=0 | | -5x+12+6x=6+x+6 | | 21+22m=35+15m | | 6w-2w+3=7w-12 | | 3X^2-18=282 |